Stemness is Derived from Thyroid Cancer Cells - Ma, Risheng; Bonnefond, Simon; Morshed, Syed A.; Latif, Rauf; Davies, Terry F. (Frontiers in Endocrinology, 2014)
Background: One hypothesis for thyroid cancer development is its derivation from thyroid cancer stem cells (CSCs). Such cells could arise via different paths including from mutated resident stem cells within the thyroid gland or via epithelial to mesenchymal transition (EMT) from malignant cells since EMT is known to confer stem-like characteristics. Furthermore, EMT is a critical process for epithelial tumor progression, local invasion, and metastasis formation. In addition, stemness provides cells with therapeutic resistance and is the likely cause of tumor recurrence. However, the relevance of EMT and stemness in thyroid cancer progression has not been extensively studied. Methods: To examine the status of stemness in thyroid papillary cancer, we employed a murine model of thyroid papillary carcinoma and examined the expression of stemness and EMT using qPCR and histochemistry in mice with a thyroid-specific knock-in of oncogenic Braf (LSL-Braf(V600E)/TPO-Cre). This construct is only activated at the time of thyroid peroxidase (TPO) expression in differentiating thyroid cells and cannot be activated by undifferentiated stem cells, which do not express TPO. Results: There was decreased expression of thyroid-specific genes such as Tg and NIS and increased expression of stemness markers, such as Oct4, Rex1, CD15, and Sox2 in the thyroid carcinoma tissue from 6-week-old BRAFV600E mice indicating the dedifferentiated status of the cells and the fact that stemness was derived in this model from differentiated thyroid cells. The decreased expression of the epithelial marker E-cadherin and increased EMT regulators including Snail, Slug, and TGF-β1 and TGF-β3, and the mesenchymal marker vimentin demonstrated the simultaneous progression of EMT and the CSC-like phenotype. Stemness was also found in a cancer thyroid cell line (named Marca cells) derived from one of the murine tumors. In this cell line, we also found that overexpression of Snail caused up-regulation of vimentin expression and up-regulation of stemness markers Oct4, Rex1, and CD15, with enhanced migration ability of the cells. We also showed that TGF-β1 was able to induce Snail and vimentin expression in the Marca cell thyroid cancer line, indicating the induction of EMT in these cells, and this induction of EMT and stemness was significantly inhibited by celastro a natural inhibitor of neoplastic cells. Conclusion: Our findings support our earlier hypothesis that stemness in thyroid cancer is derived via EMT rather than from resident thyroid stem cells. In mice with a thyroid-specific knock-in of oncogenic Braf (LSL-Braf(V600E)/TPO-Cre), the neoplastic changes were dependent on thyroid cell differentiation and the onset of stemness must have been derived from differentiated thyroid epithelial cells. Furthermore, celastrol suppressed TGF-β1 induced EMT in thyroid cancer cells and may have therapeutic potential.